MENINGKATKAN HASIL BELAJAR SENI TARI DI KELAS IV.7 SD YPPI PERAWANG KABUPATEN SIAK DENGAN METODE TUTOR SEBAYA - Mardiani Mardiani; Yuliasma Yuliasma; Herlinda Mansyur (FBS Universitas Negeri Padang, 2013)
Abstract The Dance Lessson is one of lesson in SD YPPI Perawang Especially for the class IV.7 SD YPPI Perawang. The goal of the study is to describe result in art at class IV.7 SD YPPI Perawang. For avoiding this problem, it takes the researching Class Aktivity ( PTK ) in class IV.7 for the second semester by the formula of observation in the student activity and the Learning Result Proses. By observing this research and the learning result in this case. Can use the tutorial in same age. It can improve the students learning result in class IV.7 SD YPPI Perawang.